Contamination of Hospital Inanimate Surfaces with Methicillin-Resistant Staphylococcus aureus and Extended-Spectrum Beta-Lactamase producing bacteria at Ocean Road Cancer Institute, Dar es Salaam, Tanzania - Donath Mkenda Valerian; Mtebe Majigo; Ninael Jonas; Loveness Urio; Emanuel Magembe; Reuben Abednego; Modest Benard; Doreen Kallanga; Ibrahim Mauki; Agricola Joachim (PLoS ONE, 2026)
Background Methicillin-resistant Staphylococcus aureus (MRSA) and extended-spectrum beta-lactamase (ESBL) producing bacteria are the most common contaminants on hospital surfaces. Hospitalized patients, especially those with cancer, have a higher likelihood of acquiring hospital-associated infections in a contaminated environment. Outbreaks of MRSA and ESBL-producing bacteria linked to contaminated inanimate hospital surfaces are a well-documented threat. Cancer patients, who often have prolonged hospital stays, are particularly at risk of acquiring these multidrug-resistant (MDR) infections. The immunosuppressed state of cancer patients further increases their susceptibility, resulting in higher morbidity and mortality associated with these infections. This study assessed the prevalence, antimicrobial resistance, and factors associated with contamination of inanimate hospital surfaces by MRSA and ESBL-producing bacteria. Materials and methods This was cross-sectional study conducted at Ocean Road Cancer Institute, Dar es salaam, Tanzania in March and April 2023. The surfaces were conveniently selected, and a total of 247 inanimate surface samples were collected using a sterile swab pre-moistened with sterile Trypticase soy broth. A structured data collection checklist was used to record key variables for each sampled surface. The samples were cultured on Mannitol salt agar and MacConkey agar containing 2 mg/ml of ceftazidime. Identification of the isolates were done by using VITEC MS. Methicillin-resistant Staphylococcus aureus (MRSA) and extended-spectrum beta-lactamase (ESBL) producing bacteria were confirmed phenotypically through testing with a 30 µg cefoxitin disk and the combination disk method, respectively. Antimicrobial susceptibility testing was performed using the Kirby-Bauer disk diffusion method. Logistic and modified Poisson regression analyses were performed to determine factors associated with contamination. Results A total of 247 swab samples were collected from six predetermined items; bed rails, computer keyboards, door handles, hand-washing sinks, nursing station tables, and trolleys. The proportions of MRSA and ESBL producing bacteria’ contamination were 21 (8.5%) and 63 (25.5%), respectively. Acinetobacter baumannii and Klebsiella pneumoniae were the predominant ESBL producing bacteria each accounting for 38 of the 84 isolates (45.2%). All Staphylococcus aureus isolates were identified as MRSA and were non-susceptible to at least one antimicrobial agent in three or more antibiotic classes; however, all isolates showed 100% susceptibility to linezolid. Klebsiella pneumoniae demonstrated resistance to piperacillin-tazobactam, cefepime, and ciprofloxacin, with rates ranging from 92.1% to 97.4%. Resistance to meropenem was observed in 52.6% of Klebsiella pneumoniae isolates. Hand-washing sinks were the only surface independently associated with contamination by ESBL-producing bacteria (APR 5.8, P < 0.001). Conclusion A significant proportion of inanimate hospital surfaces were contaminated with MRSA and ESBL-producing bacteria. The findings imply a need to improve infection prevention and control practices.